Trusting what you know : - Raider-Roth, Miriam B. (Jossey-Bass, 2005)
Trusting What You Know shows that building genuine trustworthy relationships between teachers and students is pivotal in students??? capacity to learn. Based on an extended research study by Miriam Raider-Roth, an educational researcher and former elementary school teacher, Trusting What You Know reveals what students think about their relationships in the classroom and how these relationships affect their ability to learn. The book includes guiding principles for teachers, researchers, educators, and parents who want to understand the ways that human relationships at school fundamentally influence what children learn, know, and trust.